Prototype of Making Semi Automatic Tofu Nigarin Using Atmega16 (Tofu Without Waste) - Adi Irawan; Haryanto; Kunto Aji Wibisono; Dian Neipa Purnamasari (Universitas Muhammadiyah Sidoarjo, 2021)
Tofu has the best quality vegetable protein because it has the most complete amino acid composition and is believed to have a relatively high digestibility of 85 - 98%. Basically, making tofu uses acidic / coagulation using vinegar, but different from tofu nigari, the coagulation process uses seawater rice extract. This material was chosen because in the process it does not produce waste and also does not smell so it is environmentally friendly. The background of making this tool is to provide learning as well as knowledge about tofu nigarin and to make prototypes so that it is easier to digest knowledge and also this tool uses a semi-automatic process, which usually makes tofu still using manual technology. For the method itself, it uses the fuzzy method, which is comparing several results to find out the right size in the manufacturing process. With this tool, it is hoped that the public will know what tofu nigarin is and can also use this tool to start their own business at home because by using this tool making tofu becomes easy.